Enhancing Postpartum Maternal Health through Educational Interventions and Non-Invasive Biomedical Immunology-Based Monitoring in Pagesangan, Kebonsari, Surabaya - Kholifatul Ummah; Arkha Rosyaria Badrus; Miftahul Khairoh; Yustisia Amalia; Cityta Putri Kwarta; Lentera Afrida Kusumawardani (Universitas STRADA Indonesia, 2025)
The maternal mortality rate (MMR) in Indonesia remains relatively high, with postpartum infection being one of the leading causes. The postpartum period is a critical phase during which physiological changes occur, increasing the risk of infection. However, the lack of adequate maternal health monitoring remains a challenge in the early detection of complications. This study aims to implement health technology-based monitoring using wearable sensors (HRV sensor/smartwatch) and axillary thermometers to detect changes in maternal body temperature and heart rate variability during the postpartum period. A total of 20 postpartum mothers, aged 2-14 days, from Pagesangan Subdistrict, were monitored for seven days. The results showed that the majority of participants (90%) were in good health; however, two participants (10%) experienced an increase in body temperature above 38°C and unstable HRV, which are early indicators of postpartum infection. These participants were immediately provided with additional health education and referred to healthcare professionals for further examination. Meanwhile, the remaining participants continued to receive routine monitoring and education regarding postpartum infection prevention. The implementation of this community service program demonstrated that health technology-based monitoring is effective in detecting real-time health condition changes, allowing for faster medical interventions and increasing maternal awareness of postpartum health. The findings suggest that this method can serve as an innovative approach to reducing postpartum infection risks and improving maternal health quality. Further development and wider application of this approach in other regions are recommended to enhance postpartum care and maternal well-being.